Native Wolbachia infection and larval competition stress shape fitness and West Nile virus infection in Culex quinquefasciatus mosquitoes - Alomar, Abdullah A.; Pérez-Ramos, Daniel W.; Kim, Dongmin; Kendziorski, Natalie L.; Eastmond, Bradley H.; Alto, Barry W.; Caragata, Eric P. (Frontiers in microbiology, 2023)
transinfections established in key mosquito vectors, including are typically associated with pathogen blocking-reduced susceptibility to infection with key pathogens and reduced likelihood those pathogens are transmitted to new hosts. Host-symbiont-virus interactions are less well understood in mosquitoes like , which naturally harbor , with pathogen blocking observed in some populations but not others, potentially due to innate differences in their load. In nature, mosquito larvae are often subject to developmental stresses associated with larval competition, which can lead to reduced body size and differential susceptibility to arbovirus infection. In this study, we sought to understand whether competition stress and infection in combine to impact host fitness and susceptibility to infection with West Nile virus. We reared -infected and uninfected larvae under three competition stress levels, increasing larval density without increasing the amount of food supplied. We then monitored larval development and survival, measured wing length and quantified density in adults, and then challenged mosquitoes from each treatment group orally with West Nile virus. We observed that high competition stress extended development time, decreased the likelihood of eclosion, decreased body size, and increased susceptibility to West Nile virus (WNV) infection. We also observed that infection reduced WNV load under low competition stress, and significantly improved the rate of survival for larval reared under higher competition stress. Consequently, our data suggest that native infection in has differential consequences for host fitness and susceptibility to WNV infection depending on competition stress.